Design and Development of Interactive Moodle using Design Thinking to Support Online Learning - Abdillah, Yan Amal; Utami, Ika Qutsiati; Setiyawan, Wahyu Beny Mukti; Pratama, Mochammad Rizal; Afani, Indra Resya; Pramesti, Ari Yohana (Elinvo (Electronics, Informatics, and Vocational Education), 2024)
Moodle is an open-source learning management system (LMS) or e-learning platform that is designed to help educators create online courses with various features to facilitate learning. Interest in this research area has increased significantly in recent years, leading to an increasing number of schools employing this LMS. In the early stages of the development process, schools need to gain insights into user needs and generate new ideas for designing and developing interactive LMS. In this light, Design Thinking (DT) is viewed as an important approach. This study aimed to design and develop an online learning system based on Moodle to facilitate online learning for elementary school students. The objectives were to (1) design a system diagram, system architecture, and functional structure for facilitating online learning and (2) develop an interactive LMS using Moodle. The research methodology was conducted following the DT process. An evaluation was made to assess the usability of the system using the Computer System Usability Questionnaire (CSUQ). Across dimensions such as system quality, information quality, and interface quality, scores ranged between 5 and 7, highlighting a positive user perception across various aspects of the evaluation. These findings, therefore, offer practical guidance for educational stakeholders in adopting and promoting Moodle-based LMS.